Peer Feedback and Speaking Anxiety in Indonesian EFL Classrooms: Students’ Narrative Perspective - Nadia Simare Mare; Grand Stefan Claudio; Ayonia Jelita Boru Sinaga; Muhammad Subhan Fikri; Olga Dona Retsi (FOSTER: Journal of English Language Teaching, 2026)
Speaking anxiety is still a big problem for EFL learners, especially when they have to speak in front of the class. The purpose of this study is to investigate how Indonesian EFL students view peer feedback and how it can help them feel less nervous when speaking. Four third-year students from Universitas Palangka Raya's English Education Study Program were purposefully chosen to participate in a qualitative narrative inquiry design. Semi-structured interviews were used to gather data, and Braun and Clarke's thematic analysis was used for analysis. The results show that students' lack of confidence, fear of making mistakes, and negative evaluation are the main causes of speaking anxiety. Peer feedback, on the other hand, makes a positive contribution by assisting students in recognizing their shortcomings, raising awareness of their speaking performance, and progressively lowering anxiety. In contrast to teacher feedback, which is valued for its precision and detail, students view peer feedback as encouraging, less frightening, and emotionally reassuring. According to the study's findings, integrating teacher and peer feedback results in a well-rounded setting that promotes both linguistic growth and emotional health. This study provides valuable insights into classroom speaking practices despite its small sample size and reliance on interview data. It also suggests that structured peer feedback can be a useful tactic for managing speaking anxiety.